Religious Values of the Nisfu Sha'ban Tradition in the Pedukuhan Kubang Tegal Community - Amar Ma'aruf; Mohammad Amas Lahat; Nanang Lidwan; Maksum Maksum (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
The aim of the research is to describe the traditions of the month of Nisfu Sya'ban, including increasing fasting and increasing good religious practices, especially during the month of Sya'ban. Because among the people, people do not agree with saying heresy. In fact, religious culture cannot be formed if religious values are not formed. This research involved fieldwork using a qualitative approach. Data collection techniques are interviews, observation and notes. The data obtained was analysed using qualitative descriptive techniques. The results of the Nisfu Sha'ban Tradition include reading the Yasin letter on Nisfu Sha’ban night, which is a very active activity. The condition of community is more interested in traditions that contain Islamic values. So with this research, the community can promote faith and increase friendship, generosity and improve the economy of the local community.